Finding Linked Markers to En for Efficient Selection of Pea Enation Mosaic Virus Resistance in Pea. Issue 6 (1st November 2013) - Jain, Shalu; Weeden, Norman F.; Porter, Lyndon D.; Eigenbrode, Sanford D.; McPhee, Kevin
ABSTRACT: Pea enation mosaic virus (PEMV) causes an important disease of cool‐season food legumes, resulting in significant yield loss worldwide. The present investigation was carried out to study the inheritance and identify the molecular markers linked with the PEMV resistance gene ( En ) in field pea ( Pisum sativum L.) using an F7 –derived mapping population developed from the cross 'Lifter' (resistant)/'Radley' (susceptible). Three hundred ninety‐three recombinant inbred lines (RILs) were phenotyped for reaction to PEMV in the field under natural inoculation and in the greenhouse using artificial inoculation. The RILs segregated in the expected 1:1 ratio for resistance and susceptibility in the field and greenhouse evaluations. Sequence tagged site markers were developed through an intron targeted amplified polymorphism approach based on comparative mapping with Medicago truncatula Gaertn. and a targeted region amplified polymorphism approach was also used to enrich the genomic region segregating for the En gene. Our results demonstrate that resistance to PEMV in pea is governed by a single gene, En, located on linkage group III between markers CNGC (2.5 cM) and tRNAMet2 (1.3 cM) with many other closely associated markers. These two markers in combination predict the presence of En with 99.4% accuracy in the Lifter/Radley mapping population and have implications for marker‐assisted selection for PEMV resistance in pea improvement breeding programs.